2013
DOI: 10.1371/journal.pone.0059095
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of HuR in Cytoplasm, but Not Nuclei, Is Associated with Malignant Aggressiveness and Prognosis in Bladder Cancer

Abstract: IntroductionHuman antigen R (HuR) regulates the stability of mRNA and is associated with cell proliferation, angiogenesis, and lymphangiogenesis. However, the clinical significance and pathological role of HuR in bladder cancer remains unclear. The main objective of this investigation was to clarify the relationships between HuR expression and clinical significance and cancer cell proliferation, angiogenesis, lymphangiogenesis, and expressions of cyclooxygenase (COX)-2 and vascular endothelial growth factor (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 23 publications
6
60
1
1
Order By: Relevance
“…Similar findings have also been observed in patients with various malignancies, including bladder cancer (8). Therefore, the pathological role and biological characteristics of HuR in Figure 1.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Similar findings have also been observed in patients with various malignancies, including bladder cancer (8). Therefore, the pathological role and biological characteristics of HuR in Figure 1.…”
Section: Discussionsupporting
confidence: 81%
“…Associations between HuR expression and response in second-line chemotherapy. numerous types of malignancy have been investigated in vivo and in vitro (5)(6)(7)(8)(9)(10)28). To the best of our knowledge, the first study that identified upregulated HuR expression as a significant marker for an improved response to GEM-based chemotherapy in patients with pancreatic cancer was published in 2009 (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations